The Influence of the Cooperative Learning Model on Class Students' Mathematics Learning Motivation - Farah Nabila Maulida; Manurung, Alberth Supriyanto (ITScience (Information Technology and Science), 2024)
The results of this research were motivated by the low learning motivation of class IV students at SDN 05 Tanjung Duren Selatan which resulted in 47% of students getting scores below the KKM with an average of 69 on the mathematics exam. This research used a quantitative approach with a survey method and the population used was 30 students, including 15 class IVA students and 15 class IVB students. The data collection technique in this research used a questionnaire and the application of trimino media with a cooperative learning model. Based on the calculations above, it is found in the table that it is 2,084 and tcount is 4,477 > 2,084 table with a significance of 0.00 < 0.05 which shows that it rejects ???????? and accepts ????????, which means there is an influence on the learning motivation of class IV students when studying by implementing the Cooperative learning model with the help of Trimino Media. The researcher was able to draw the following conclusions from the data analysis: the cooperative learning model with Trimino media has a positive and significant influence on students' mathematics learning motivation, based on partial test results.